Desenvolvimento de peptídeos miméticos a um inibidor de Fosfolipases A2 por Phage Display com potencial para aplicações terapêuticas - Costa, Kellen Cristina Torres (2022)
Phospholipase A2 (PLA2) is an important family of enzymes implicated in various biological functions. The secreted PLA2s (sPLA2s) are found in vertebrate and invertebrate secretions, such as snake venom, which is the most studied type due to its potential biotechnological application, since PLA2 expression is increased in inflammatory diseases and some cancers. Our aim was to select PLA2 inhibitor mimetic peptides through Phage Display (PhD) with antitumor and anti-inflammatory actions. Mimetic peptides to PLA2 inhibitor were selected using BpPLA2-TXI, a PLA2 isolated from Bothrops pauloensis and γCdcPL, a PLA2 inhibitor isolated from Crotallus durissus collilineatus which was used as a competitor during elution step. We have selected 2 peptides, C2PD and PepSeq9 (which was modificated through bioinformatics). The C2PD peptide tested in PBMC significantly down-modulated IL-6 and IL-1β and up-regulated IL-10 responses, besides reduced PLA2 activity. The PepSeq9 peptide seems to be a PLA2 ligand and it was cytotoxic to MDA-MB-231, a triple-negative breast cancer cell line, besides revealing a non-cytotoxic effect in Vero cells, a monkey kidney cell line. We suggest that C2PD and PepSeq9 peptides may have a potential role in inflammatory and tumoral diseases treatments, respectively.